Chapter 11 - Dynamics and innovative technologies affecting diets: implications on global food and nutrition security - Descalzo, Adriana Maria (2021)
Consumers are increasingly aware of the influence of diet on their health and require products that contribute to their well-being. The food security concept requires increased knowledge about minor components in the diet as micronutrients, vitamins, bioactive compounds together with fatty acids, which are naturally present in food and exert biological effects to improve human health. This chapter provides an insight into the physiological function of the body and the biochemical function of the fatty acids and polar lipids. It discusses the significance of health-related fatty acids, their presence in food and consumption, and how all these factors help in achieving food and nutrition security. In addition, an approach to some food processing and preservation technologies is presented. Resumen: Los consumidores son cada vez más conscientes de la influencia de la dieta en su salud y necesitan productos que contribuyan a su bienestar. El concepto de seguridad alimentaria requiere un mayor conocimiento de los componentes menores de la dieta como micronutrientes, vitaminas, compuestos bioactivos y ácidos grasos, que están presentes de forma natural en los alimentos y ejercen efectos biológicos para mejorar la salud humana. Este capítulo proporciona información sobre la función fisiológica del cuerpo y la función bioquímica de los ácidos grasos y los lípidos polares. Se analiza la importancia de los ácidos grasos relacionados con la salud, su presencia en los alimentos y el consumo, y cómo todos estos factores ayudan a lograr la seguridad alimentaria y nutricional. Además, se presenta un enfoque de algunas tecnologías de procesamiento y conservación de alimentos.